"Children trade" and national pride: juvenile emigration regulation between the Italian Unity and the law of 1901 (Italian Review of Legal History, 2019)
The essay investigates the Italian juvenile emigration regulation between the country Unity and the enactment of the emigration law of 1901. After highlighting the existence of an ancient tradition of juvenile emigration, dating back to the Ancien Règime movements of labourers for working purposes inside and outside the Italian area, the paper describes the first norms enacted to face juvenile emigration and child labour abroad.     Following to the first reports about the “children trade” in the ‘60s of the 19th century and the consequent debate about hard work and life conditions of little street musicians and animal trainers roaming the streets of the European and American cities, Italian politics couldn’t help facing the problem. While newspapers and novels told about ill-treated, beated and abandoned children by exploiters who kept them as slaves, since 1862 some consular reports officially put the problem to the attention of the Italian Government. But the indignation and concern for the exploitation of children was accompanied by a greater worry for the image of the country abroad, spoiled by the presence of such tramps and beggars in the streets of the main cities of the Old Continent and the New World.     Notwithstanding the mentioned reports, the political debate was destined to produce no practical effects for long. While during the ’70s of the 19th century some administrative acts were enacted by Government to control and repress emigration (the Circolare Menabrea, enacted in 1868 after the report in Parliament of the first alarming data about the expatriations, the Circolare Lanza of 1873 and the Circolare Nicotera, three years later), a proper law facing the problem of juvenile emigration and children exploitation abroad was promulgated in 1873. The Law n. 1733 of 1873 enacted that whoever employed minors of eighteen years in the Italian Reign and abroad as acrobats, charlatains, musicians or animal trainers, beggars and similar activities, would be imprisoned and fined. Penalties would be increased in case under age children had been abandoned and ill-treated. The law finally enacted that all children employed in strolling professions should be repatriated and returned to their families. The norms, which didn’t face the child labour problem in general and were only directed to repress a shamefull phenomenon, soon revealed to be inadequate and ineffective.Notwithstanding the poor interest on the part of Government for juvenile emigration and child labour conditions, the problem of the street musicians contributed to draw the attention on the exploitation of children in the European factories. While since the ’40s of the 19th century some European countries had already enacted the first laws aimed to regulate and protect child labour, in Italy only in the ’70s the matter started to be faced and a first law concerning it was promulgated only in 1886. In fact, not only children work was considered fundamental for the industrial development in the years following the country Unity, but the recourse to it in the factories was reputed as the only possible alternative to the wandering life that the measures converning strolling professions had intended to hit. Such an attitude would affect the discipline of child labour in the country for a long time.     In 1895 a new consular report highlighted the high number of Italian children employed in the French glassworks: it was a very hard work for the little emigrants, usually destined to the most laborious and dangerous duties. After two Government enquiries, politics could not ignore the problem of juvenile emigration and child labour anymore. The “social” law on emigration of 1901, directed – differently from the first law in the matter of 1888 - to protect and not to repress emigration anymore, would represent a turning point in the discipline of children expatriations. In fact, the law enacted that whoever employed children under the age of fifteen both in strolling professions and in dangerous and harmful manufactures abroad, would be imprisoned and fined. The same punishments were provided for whoever induced a girl under age to emigrate and prostitute herself. Such punishments were increased in case of ill-treatment and torture to children. The law of 1901 would be soon followed by other norms directed to protect child and women labour.
Keywords: Juvenile trade; Emigration legislation; Juvenile emigration